Discourse Analysis of Online News on The Pesut Samarinda Mountain: Teun A. Van Dijk’s Model - Taqdiraa Taqdiraa; Yusak Hudiyono (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2025)
This study aims to analyze online news discourse surrounding the polemic of the construction of the Pesut Mahakam Monument in Samarinda City using Teun A. van Dijk’s critical discourse analysis model. This model consists of three main aspects: text structure (macrostructure, superstructure, and microstructure), social cognition (how news is constructed by the media), and social context (how social, political, and economic factors influence news discourse). The research data were obtained from five online media sources: suaralkaltim.id, kaltimpost.id, tribunjatim.com, kaltimfaktual.co, and kompas.com.The analysis reveals that the media discourse tends to construct a narrative of criticism toward the monument's design, which is considered unclear in representing the Pesut Mahakam figure. In addition, public attention is also focused on the transparency of the project’s budget, which amounts to IDR 1.1 billion. The majority of the public and art observers tend to support the criticisms of the project, while the government emphasizes aspects of urban revitalization and artistic value.Through this analytical approach, it is found that the use of language in online news plays a significant role in shaping public opinion regarding urban icon development projects. This study also highlights the importance of public participation and budget transparency in urban development initiatives to prevent prolonged polemics in the future. The findings contribute to a deeper understanding of the media's role in shaping public perception and the necessity of transparency and inclusive governance in regional development planning.